No evidence for bilingual cognitive advantages: A test of four hypotheses - von Bastian, Claudia C; Souza, Alessandra S; Gade, Miriam (Journal of experimental psychology. General, 2016)
The question whether being bilingual yields cognitive benefits is highly controversial with prior studies providing inconsistent results. Failures to replicate the bilingual advantage have been attributed to methodological factors such as comparing dichotomous groups and measuring cognitive abilities separately with single tasks. Therefore, the authors evaluated the 4 most prominent hypotheses of bilingual advantages for inhibitory control, conflict monitoring, shifting, and general cognitive performance by assessing bilingualism on 3 continuous dimensions (age of acquisition, proficiency, and usage) in a sample of 118 young adults and relating it to 9 cognitive abilities each measured by multiple tasks. Linear mixed-effects models accounting for multiple sources of variance simultaneously and controlling for parents' education as an index of socioeconomic status revealed no evidence for any of the 4 hypotheses. Hence, the authors' results suggest that bilingual benefits are not as broad and as robust as has been previously claimed. Instead, earlier effects were possibly due to task-specific effects in selective and often small samples.